Linguistic Legitimacy and Social Justice - Reagan, Timothy (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
'This book provides the first comprehensive study of language legitimacy and social justice. It tackles the very real problem of language prejudice and offers solutions to dealing with this problem. Dr. Reagan has spent his entire career debunking misconceptions about the "value" of one language or one dialect over another and consolidates his findings here with reference to a substantial body of previous research covering a wide variety of languages.' -Frank Nuessel, University of Louisville, USA This book examines the nature of human language and the ideology of linguistic legitimacy - the common set of beliefs about language differences that leads to the rejection of some language varieties and the valorization of others. It investigates a broad range of case studies of languages and dialects which have for various reasons been considered 'low-status' including: African American English, Spanglish, American Sign Language, Yiddish, Esperanto and other constructed languages, indigenous languages in post-colonial neo-European societies, and Afrikaans and related language issues in South Africa. Further, it discusses the implications of the ideology of linguistic legitimacy for the teaching and learning of foreign languages in the US. Written in a clear and accessible style, this book provides a readable and pedagogically useful tool to help readers comprehend the nature of human language, and the ways in which attitudes about human language can have either positive or negative consequences for communities and their languages. It will be of particular interest to language teachers and teacher educators, as well as students and scholars of applied linguistics, intercultural communication, minority languages and language extinction. Timothy Reagan is the Dean of the College of Education and Human Development and Professor of Linguistics at The University of Maine, USA. .